Comparison of Bead-Based Fluorescence Versus Planar Electrochemiluminescence Multiplex Immunoassays for Measuring Cytokines in Human Plasma - Günther, Anna; Becker, Matthias; Göpfert, Jens; Joos, Thomas; Schneiderhan-Marra, Nicole (Frontiers in Immunology, 2020)
This study compared two 96-well multiplex immunoassay platforms for analytical performance in assessing cytokine concentrations in standards, quality controls and human plasma samples (n=62), and evaluated assay time requirements. Assays included a bead-based fluorescence MILLIPLEX® assay/Luminex fluorescence platform (LMX) and 3 kits from Meso Scale Discovery (MSD) in planar electrochemiluminescence format. The LMX kit evaluated 21 cytokines and the MSD kits evaluated 10 cytokines each, with 16 overlapping cytokines between platforms. Both assays provided good reproducibility in standard curves for all analytes. Interassay CVs of shared analytes showed average kit quality control CVs ranging 1.9‒18.2% for LMX and 2.4‒13.9% for MSD. The MSD platform had lower LLoQs than LMX for 14/16 shared cytokines. For IL-17, the LLoQ was lower with LMX than MSD, and the LLoQs for IL-6 were similar. Although MSD calibration curves indicated lower LLoQs for most of those analytes, many more cytokines in human plasma samples were not detected by MSD than by LMX. The ULoQs were higher in LMX versus MSD assays for 13/16 shared analytes, lower than MSD for IL-17, and equivalent between assays for IL-6 and MIP-1α. Bland Altman plots indicated that MSD classified 13/16 shared analytes as concentrations lower than by LMX. Time and motion analysis indicated that total mean assay times were 20h 28m and 21h 33m for LMX and MSD, respectively, including an overnight (17 hour) incubation. Hands-on labor time averaged 1h 37m for LMX and 2h 33m for MSD. In summary, assay selection factors should include selection of specific markers of interest, time and cost considerations, and anticipated cytokine concentrations in prospective samples.